PECULIARITIES OF COOPERATION BETWEEN TURKEY AND THE EUROPEAN UNION IN MODERN INTERNATIONAL RELATIONS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Trade relations between Turkey and the European Union are a complex and multifaceted topic. Mutual economic interests, political differences and historical ties determine the dynamics of trade relations between the two countries. This article attempts to comprehensively study the internal political struggle in Turkey, bilateral trade relations, migration issues, the country's accession to the European Union, the positions of pro-Western politicians and their opposition to the West. The results of the study allow us to reflect on the socio-political processes in Turkey in connection with the choice of the pro-European path. In addition, the strategy of energy exchange between Turkey and the European Union is explained in detail.